Consequences of Brexit and Options for a "Global Britain" - Steven Brakman; Harry Garretsen; Tristan Kohl (Center for Economic Studies and ifo Institute (CESifo), 2017)
The United Kingdom has opted to leave the European Union. The trade and welfare consequences of this decision are large; most studies predict a trade and welfare loss for both the UK and the EU. The UK parliament has indicated that it aims for new and ambitious trade agreements following Brexit, but has not been explicit what type of trade agreements it envisions (except that it should be broad) or with whom specifically. In this paper, we consider the UK's options. We first confirm, in line with existing studies, that the negative trade consequences of Brexit are substantial, especially for the UK and also for the EU. After reviewing all potential options, we have a simple answer to the question whether the UK has an alternative for the existing trade agreement with the EU. The answer is: No. Only a trade agreement with the EU can compensate for the negative trade consequences of Brexit.
Keywords: F13; F14; 330; Brexit; Gravity Model; trade predictions